Fashion Streetwear Sebagai Penunjang Musisi Indie di Kota Bandung (1990-2004) - Indar Buana Pradipta; Reiza D. Dienaputra; Ayu Septiani (Titian: Jurnal Ilmu Humaniora, 2021)
This thesis is titled "Fashion streetwear as a support for indie musicians in the city of Bandung; 1990-2008". The Focus of the discussion is how fashion streetwear can be a support in the sustainbility of indie musicians in the city of Bandung. This research uses a historical method in which there are have several work steps such as field studies, literature studies, and interviews as supporting instruments. The historical method has four stages of work namely heuristics,criticism, interpretation, and historiography. The method the author uses as an analytical tool to dissect the problems discussed plus the help of other scientific concepts such as sociology, economics, and communication. The fact found is that, streetwear fashion began to develop in the City of Bandung in 1990's. The driving factors for the growth of this fashion trend include the development of indie music, and the incresing independent spirit in Bandung which eventually triggers the emergence of local fashion brands in Bandung, to become dominant culture for the city's young people and consistently supporting indie musicians in the Bandung City.